2019
DOI: 10.1111/jcmm.14168
|View full text |Cite
|
Sign up to set email alerts
|

CCL18 promotes the metastasis of squamous cell carcinoma of the head and neck through MTDH‐NF‐κB signalling pathway

Abstract: Metastasis is one of the primary causes for high mortality in patients with squamous cell carcinoma of the head and neck (SCCHN). Our previous study showed that chemokine (C‐C motif) ligand 18 (CCL18), derived from tumour‐associated macrophages (TAMs), regulates SCCHN metastasis by promoting epithelial‐mesenchymal transition (EMT) and preserving stemness. However, the underlying mechanism needs to be further investigation. Interestingly, metadherin (MTDH) expression was induced when SCCHN cells were stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…NF‐κB is closely associated with the progression of numerous cancers . ANXA2 is closely associated with NF‐kB pathway .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NF‐κB is closely associated with the progression of numerous cancers . ANXA2 is closely associated with NF‐kB pathway .…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB signalling is associated with numerous of cellular responses, such as cell survival, differentiation and proliferation. 25 NF-κB signalling has been reported to play an vital role in malignant cell mobility. 34,35 Recent studies showed ANXA2 could mediate upregulation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28]38,39 However, there is still little evidence defining the role of LINC00511 in EMT. [26][27][28]38,39 However, there is still little evidence defining the role of LINC00511 in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the long non-coding RNA (lncRNA) RP11 promotes colorectal cancer cells dissemination by ZEB1 overexpression, whereas lncRNA HCCL5 could be activated by ZEB1 to promote hepatocellular carcinoma malignancy. 18,19 Among these, lncRNAs are a class of ncRNAs of more than 200 bp that have been demonstrated to be closely related to cancer progression, including tumorigenesis, 20 stemness, 21 apoptosis, 22 25 It has also been reported that LINC00511 promotes proliferation in pancreatic ductal adenocarcinoma, 26 ovarian cancer 27 and glioma. 16,17 Non-coding RNAs (ncRNAs) are transcribed genes that are not further translated into proteins and include lncRNAs, circular RNAs (circRNAs) and miRNAs, which perform vital roles in human cancers.…”
mentioning
confidence: 99%